Combination of pioglitazone and dendritic cell to optimize efficacy of immune cell therapy in CT26 tumor models - Samaneh Tokhanbigli; Helia Alavifard; Hamid Asadzadeh Aghdaei; Mohammad Reza Zali; Kaveh Baghaei (BioImpacts, 2023)
Introduction: The maturation faith of dendritic cells is restrained by the inflammatory environment and cytokines, such as interleukin-6 and its downstream component. Therefore, introducing the suitable antigen to dendritic cells is crucial. However, reducing the severity of the suppressive tumor microenvironment is indispensable. The present study examined the combination therapy of lymphocyte antigen 6 family member E (LY6E) pulsed mature dendritic cells (LPMDCs) and pioglitazone against colorectal cancer (CRC) to elevate the effectiveness of cancer treatment through probable role of pioglitazone on inhibiting IL-6/STAT3 pathway. Methods: Dendritic cells were generated from murine bone marrow and were pulsed with lymphocyte antigen 6 family member E peptide to assess antigen-specific T-cell proliferation and cytotoxicity assay with Annexin/PI. The effect of pioglitazone on interleukin (IL)-6/STAT3 was evaluated in vitro by real-time polymerase chain reaction (PCR). Afterward, the CRC model was established by subcutaneous injection of CT26, mouse colon carcinoma cell line, in female mice. After treatment, tumor, spleen, and lymph nodes samples were removed for histopathological, ELISA, and real-time PCR analysis. Results: In vitro results revealed the potential of lysate-pulsed dendritic cells in the proliferation of double-positive CD3-8 splenocytes and inducing immunogenic cell death responses, whereas pioglitazone declined the expression of IL-6/STAT3 in colorectal cell lines. In animal models, the recipient of LPMDCs combined with pioglitazone demonstrated high tumor-infiltrating lymphocytes. Elevating the IL-12 and interferon-gamma (IFN-γ) levels and prolonged survival in lysate-pulsed dendritic cell and combination groups were observed. Conclusion: Pioglitazone could efficiently ameliorate the immunosuppressive feature of the tumor microenvironment, mainly through IL-6. Accordingly, applying this drug combined with LPMDCs provoked substantial CD8 positive responses in tumor-challenged animal models.